2008
DOI: 10.1002/eji.200738000
|View full text |Cite
|
Sign up to set email alerts
|

Glycolipid‐activated NKT cells support the induction of persistent plasma cell responses and antibody titers

Abstract: NKT cell activation with CD1d-binding glycolipid a-galactosylceramide (a-GC) enhances antibody responses to co-administered T-dependent antigen. The efficacy of a-GC relative to other CD1d-binding glycolipids and adjuvants is not known. There is little information on how NKT cells affect antibody production beyond initial booster-stimulated recall responses. We therefore tested the hypothesis that a-GC stimulates induction of plasma cells and antibody responses as effectively as Th1-and Th2-skewing variants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
79
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 43 publications
8
79
0
Order By: Relevance
“…Immulon 4 enzyme-linked immunosorbent assay (ELISA) plates (Dynex, Chantilly, VA) were coated with CTD1 or CTD2, and specific endpoint IgG1, IgG2b, IgG2c, and IgG3 titers were determined as described previously (39). In adoptive transfers, IgH b was also detected by ELISA as described previously (37).…”
Section: Methodsmentioning
confidence: 99%
“…Immulon 4 enzyme-linked immunosorbent assay (ELISA) plates (Dynex, Chantilly, VA) were coated with CTD1 or CTD2, and specific endpoint IgG1, IgG2b, IgG2c, and IgG3 titers were determined as described previously (39). In adoptive transfers, IgH b was also detected by ELISA as described previously (37).…”
Section: Methodsmentioning
confidence: 99%
“…Coadministration of a-GC with immunizing antigen to mice results in enhanced production of antibodies specific for the antigen [170][171][172], demonstrating that the adjuvant effect of iNKT cells is antigen-specific. This help provided by iNKT cells results in the induction of long-lived antibody-secreting plasma cells, affinity maturation and the generation of memory B cells [172][173][174][175]. iNKT cells can also provide help for B cells specific for lipid-containing antigens internalized through the B cell receptor [176,177].…”
mentioning
confidence: 99%
“…However, unlike other classic adjuvants, αGalCer was shown to enhance Ab production against both TD and TI Ags also in mice lacking CD4 + Th cells [34,35], suggesting the possible provision of CD1-dependent B-cell help by iNKT cells in vivo. Immunization of mice lacking iNKT cells revealed that iNKT cells also display a spontaneous (non-αGalCer induced) role in inducing and/or maintaining the circulating Ab levels through the control of plasma cell homeostasis [34,36], which was found to depend on the iNKT-cell expression of B-cell activating factor and a proliferation-inducing ligand (APRIL) [37]. …”
mentioning
confidence: 99%